2023
DOI: 10.3389/fmicb.2022.1060050
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of extended-spectrum β-lactamases in Enterobacterales in Taiwan for over two decades

Abstract: The emergence of antimicrobial resistance among microorganisms is a serious public health concern, and extended-spectrum β-lactamases (ESBL)-producing Enterobacterales is one of the major concerns among antibiotic-resistant bacteria. Although the prevalence of ESBL in Enterobacterales has been increasing with time, the prevalence of ESBL could differ according to the species, hospital allocation, sources of infections, nosocomial or community acquisitions, and geographic regions. Therefore, we conducted a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…For example, a higher frequency of Eco-ESBL has been reported in Southeast Asia, Africa, and Central America compared with Europa [ 5 , 24 ]. Similarly, the rates of ESBL-PE are higher in northern regions than in other parts of Taiwan [ 25 ], and a study from the USA (overall prevalence of 11%) showed that while ESBL-PE prevalence was 5% in Michigan, in Washington, DC, it was 26% [ 26 ]. In terms of patient populations, infections caused by ESBL-PE are most commonly seen in hospitalized patients, particularly those with underlying medical conditions, those with immunocompromised status, and those who have been exposed to invasive medical procedures or devices, such as those in intensive care units.…”
Section: The Epidemiology Of Esbl-pe Before the Covid-19 Pandemicmentioning
confidence: 99%
“…For example, a higher frequency of Eco-ESBL has been reported in Southeast Asia, Africa, and Central America compared with Europa [ 5 , 24 ]. Similarly, the rates of ESBL-PE are higher in northern regions than in other parts of Taiwan [ 25 ], and a study from the USA (overall prevalence of 11%) showed that while ESBL-PE prevalence was 5% in Michigan, in Washington, DC, it was 26% [ 26 ]. In terms of patient populations, infections caused by ESBL-PE are most commonly seen in hospitalized patients, particularly those with underlying medical conditions, those with immunocompromised status, and those who have been exposed to invasive medical procedures or devices, such as those in intensive care units.…”
Section: The Epidemiology Of Esbl-pe Before the Covid-19 Pandemicmentioning
confidence: 99%
“…Furthermore, a clonal sequence type of O25b-ST131 has emerged among urine or bloodstream E. coli isolates in the Taiwanese community, and this clone has been linked to toxicity, ESBL (CTX-M-15) expression, ciprofloxacin resistance, and fatality. [6] Reports from the early 2000s revealed that CTX-M-producing strains were spreading throughout Europe, Latin America, and the Asia-Pacific region. TEM-and SHV-type enzymes were once the most common ESBLs globally.…”
Section: Content 21 Antibiotic and Antibiotic Resistancementioning
confidence: 99%